AN INTERMEDIATE TARGET FOR THE SBP: HEADLINE OR CORE INFLATION? - Fatima Khaliq (International Journal of Contemporary Issues in Social Sciences, 2023)
The choice of inflation measure to target (headline vs. core) has always been an important policy question for inflation targeting central banks amid the potential second round effects from food and energy prices. This paper investigates the same for Pakistan using SVAR and identifying the exogenous shocks to the food, and energy prices and the transmission of these shocks to the rest of the economy. The paper finds evidence of strong transmission from food price shocks to the headline inflation and inflation expectations in Pakistan over the sample of 2009 – 2022 suggesting to target headline inflation over the medium term.